2019
DOI: 10.1177/1369433219895918
|View full text |Cite
|
Sign up to set email alerts
|

Application of innovative one-dimensional periodic isolation systems for seismic response reduction of bridges

Abstract: This article deals with structural vibration attenuation and control using periodic materials for isolation of structures. An innovative approach to achieve wider low-frequency attenuation zones using a combination of different one-dimensional periodic units has been explored to provide close to a vibration-free environment for civil engineering structures subjected to seismic and other excitations. The wave attenuation regions for the base isolation system made of periodic materials have been derived from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…The extension of the specific concept in the two-dimension [11] and three-dimension [12] wavefields followed later, also taking into consideration the soilstructure interaction [13] and the impact of geometrical parameters on the characteristics of the attenuation zones [14]. Applications of this concept included the dynamic responses of a multi-story frame building [15] and the seismic response reduction in bridges [16]. The development of a non-linear periodic foundation for the same purpose has been conducted recently [17], placing roller bearings between the concrete layers of the foundation.…”
Section: Introductionmentioning
confidence: 99%
“…The extension of the specific concept in the two-dimension [11] and three-dimension [12] wavefields followed later, also taking into consideration the soilstructure interaction [13] and the impact of geometrical parameters on the characteristics of the attenuation zones [14]. Applications of this concept included the dynamic responses of a multi-story frame building [15] and the seismic response reduction in bridges [16]. The development of a non-linear periodic foundation for the same purpose has been conducted recently [17], placing roller bearings between the concrete layers of the foundation.…”
Section: Introductionmentioning
confidence: 99%
“…Kang et al [24] studied the influence of elastic support on dynamic property and dynamic response of arch structure under blast impact load, and the results showed that the vibration isolation of reasonable stiffness improved the anti-explosion bearing capacity of structure effectively. At present, relevant studies mainly focus on isolation of the vibration load caused by earthquakes in civil buildings, subways, and highway bridges on the ground [25][26][27][28][29][30], and various vibration isolation devices including elastic support have different effects, but all can reduce vibration damage to different degrees, while there are few studies on the vibration isolation of underground arch structures under the action of the penetration and explosion of precision-guided earthboring projectiles [31][32][33]. ere is an obvious difference between the effect of weapon strike and the earthquake load, and the effect of elastic support on reducing the vibration damage caused by weapon strike is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…According to the spatial periodicity, PIFs can be divided into three types: one-dimensional PIFs (1D PIFs), two-dimensional PIFs (2D PIFs), and three-dimensional PIFs (3D PIFs), as shown in Figure 1(b). 1D PIFs were studied by Shi et al (2014), Witarto et al (2019), Xiang et al (2012) and Jain et al (2019), and they found that a 1D PIF can generate wide AZs. However, the displacement responses of 1D PIFs increase under the action of earthquakes due to the lack of horizontal stiffness, resulting in hidden problems in practical applications.…”
Section: Introductionmentioning
confidence: 99%